Detection of electromagnetic anomalies over seismic regions during two strong (MW > 5) earthquakes - Recchiuti, D.; D’Angelo, G.; Papini, E.; Diego, P.; Cicone, A.; Parmentier, A.; Ubertini, P.; Battiston, R.; Piersanti, M. (Frontiers in Earth Science, 2023)
Ionospheric disturbances (such as electromagnetic emissions) in connection to strong earthquakes have been reported in literature for over two decades. In order to be reliable, the identification of such disturbances requires a preliminary robust definition of the ionospheric background in the absence of both seismic activity and any other possible input (e.g., transient change in solar activity). In this work, we present a new technique for the assessment of the electromagnetic (EM) background in the ionosphere over seismic regions. The background is estimated via a multiscale statistical analysis that makes use of most of the electric- and magnetic-field datasets (2019–2021) from the China Seismo-Electromagnetic Satellite (CSES-01). The result is a map of the average relative energy in a 6° x 6° LAT-LON cell centered at the earthquake epicenter (EE). Only EM signals that statistically differ from the background should be considered as events suitable for investigation. The method is tested against two strong seismic events, the 14 August 2021 Haitian earthquake (7.2 MW) and the 27 September 2021 Cretan earthquake (6.0 MW). In the former case, a signal (with characteristic frequency of 250 Hz) can be identified, which emerges from the background. In the latter one, the concurrent strong geomagnetic activity does not allow to tell any distinct signal apart from the background.